TINJAUAN YURIDIS TERHADAP KEWENANGAN KOMISI KEJAKSAAN REPUBLIK INDONESIA BERDASARKAN PERATURAN PRESIDEN NOMOR 18 TAHUN 2011 TENTANG KOMISI KEJAKSAAN REPUBLIK INDONESIA - Samuel Hamonangan Simanjuntak; Dessy Artina; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The establishment of the Prosecutorial Commission is mandated by Article 38 of LawNumber 16 of 2004 concerning the Prosecutor's Commission of the Republic of Indonesia,which implies the establishment of Presidential Regulation Number 18 of 2005 concerningthe Prosecutor's Commission of the Republic of Indonesia and in its development theregulation was changed to Presidential Regulation Number 18 of 2011 concerning theRepublican Prosecutor's Commission Indonesia. Based on the Presidential regulation, theempirical fact that the Prosecutor's Commission has many limitations as a manifestation ofweaknesses over its authority, is certainly not in line with the initial establishment of theProsecutor's Commission as an external supervisor of the Prosecutor's Commission, which isexpected to be an answer to public unrest. The inconsistency of several articles with otherarticles resulted in contradictions in their implementation, the weakness of recommendationssubmitted by the Prosecutor's Commission was practically redundant, lengthy andcomplicated the flow of handling to follow up on community reports, which made theProsecutor's Commission powerless and non-screened as external supervisors for theProsecutor's Commission. Even though the complicated and extensive task given to theProsecutor's Commission is not comparable to its limited and very weak authority to the sizeof the Prosecutorial Commission as a supervisory institution.The purpose of this study, namely: First, to find out and analyze the authority andweaknesses of the authority of the Republic of Indonesia Prosecutor's Commission based onPresidential Regulation Number 18 of 2011 concerning the Prosecutor's Commission of theRepublic of Indonesia, Secondly, to know and analyze ideal structuring ideas from theauthority of the Indonesian Prosecutor's Commission . The type of research used is normativelegal research or library legal research using research methods on legal principles.From the results of the problem research there are two main things that can beconcluded. First, the Prosecutor's Commission's authority has limitations as a form ofweakness in the authority of the Prosecutor's Commission based on Presidential RegulationNumber 18 of 2011 concerning the Prosecutor's Commission of the Republic of Indonesia,which does not provide certainty because there are several articles that are not synchronousand contradictory to their implementation in the field. following up on long-term publicreports tends to be redundant and the public will prefer to report directly to the attorney'sinternal supervisors. Second, the idea of an ideal arrangement of the authority of theProsecutor's Commission is to reinterpret this authority, by positioning itself in a more activeposition, then making changes to its authority and providing reinforcement ofrecommendations to those submitted by the Prosecutor's Commission.Keywords: Authority - Weakness of Authority - Idea for Ideal Arrangement